Effect of Nanocrystal Cellulose Isolated from Empty Fruit Bunches (Elaeis Guineensis Jack) Addition on Morphological and Mechanical Properties of Natural Rubber Latex Product. - Marpongahtun (Journal of Chemical Natural Resources, 2020)
The research about the effect of the addition of nano crystal cellulose (NCC) isolated from empty palm bunches (EPB) on the morphological and mechanical properties of natural rubber latex products was successfully conducted. This research was carried out in three steps: i.e isolation of α-cellulose from EPB, followed by isolation NCCs from α-cellulose using H2SO4 48.84% at 45ºC for 25 minutes, and manufacture of latex compound with varying filler NCC were 0, 0.6, 1.2, 1.8, 2.4, and 3.0. Manufacturing of natural rubber product was made with pour the NRL followed by vulcanized at 120ºC for 30 minutes. The sheet of NRL product was produced later characterized its mechanical properties through tensile test and surface morphology analysis by SEM. The optimum value of the tensile test result of the NRL product sheet was at the addition of 1,2 phr of NCC with values of tensile test, elongation at break, and Young’s modulus was 3.771 MPa, 877%, and 0.430 Mpa respectively. In addition, surface morphology analysis showed that the NCC was spread evenly.